Metabolic Changes Associated With Muscle Expression of SOD1G93A - Dobrowolny, Gabriella; Lepore, Elisa; Martini, Martina; Barberi, Laura; Nunn, Abigail; Scicchitano, Bianca Maria; Musarò, Antonio (Frontiers in Physiology, 2018)
Amyotrophic lateral sclerosis (ALS) is a severe neurodegenerative disorder, classified into sporadic or familial forms and characterized by motor neurons death, muscle atrophy, weakness, and paralysis. Among the familial cases of ALS, approximately 20% are caused by dominant mutations in the gene coding for superoxide dismutase (SOD1) protein. Of note, mutant SOD1 toxicity is not necessarily limited to the central nervous system. ALS is indeed a multi-systemic and multifactorial disease that affects whole body physiology and induces severe metabolic changes in several tissues, including skeletal muscle. Nevertheless, whether alterations in the plasticity, heterogeneity, and metabolism of muscle fibers are the result of motor neuron degeneration or alternatively occur independently of it remain to be elucidated. To address this issue, we made use of a mouse model (MLC/SOD1G93A) that overexpresses the SOD1 mutant gene selectively in skeletal muscle. We found an alteration in the metabolic properties of skeletal muscle characterized by alteration in fiber type composition and metabolism. Indeed, we observed an alteration of muscle glucose metabolism associated with the induction of Phosphofructokinases and Pyruvate dehydrogenase kinase 4 expression. The upregulation of Pyruvate dehydrogenase kinase 4 led to the inhibition of Pyruvate conversion into Acetyl-CoA. Moreover, we demonstrated that the MLC/SOD1G93A transgene was associated with an increase of lipid catabolism and with the inhibition of fat deposition inside muscle fibers. All together these data demonstrate that muscle expression of the SOD1G93A gene induces metabolic changes, along with a preferential use of lipid energy fuel by muscle fibers. We provided evidences that muscle metabolic alterations occurred before disease symptoms and independently of motor neuron degeneration, indicating that skeletal muscle is likely an important therapeutic target in ALS.